Pengaruh Kegiatan Steam Sederhana terhadap Kreativitas Anak Usia Dini di TK Damhil Kota Gorontalo - Elva M. Sumirat; Iyan Indriani; Sindi Adjaan; Laila Herdi; Cintami Anggriani Monggi; Adriana Moodiyato (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
This study aims to determine the effect of simple STEAM activities on the creativity of early childhood at TK Damhil Gorontalo City. The research method used is quantitative with ex-post facto type, with 15 children as respondents consisting of 6 boys and 9 girls, selected through total sampling technique. The research instruments used were the STEAM Learning Implementation Scale and Early Childhood Creativity Scale which had been tested for validity and reliability. Data analysis was performed using simple linear regression with the SPSS version 26.0 program. The results showed that the implementation of STEAM activities was mostly in the low category (53.3%), while children's creativity was dominated by the moderate category (46.7%). The hypothesis test proves that there is a positive and significant effect of STEAM activities on children's creativity with F=3876.420 and p=0.000. The influence coefficient is 0.342 and the R Square value is 0.215, indicating that about 21.5% of the variation in children's creativity can be explained by STEAM activities. Based on the research results, it is suggested that teachers optimize the implementation of simple STEAM activities so that the creative potential of early childhood can develop optimally.